Báo cáo tiếp thu, giải trình ý kiến thẩm định của Bộ Tư pháp đối với Dự án Luật Phòng thủ dân sự (Số: 2248/BC-BQP) - Bộ Quốc phòng (2022)
Toàn văn Báo cáo tiếp thu, giải trình ý kiến thẩm định của Bộ Tư pháp đối với Dự án Luật Phòng thủ dân sự (Số: 2248/BC-BQP)